PENGARUH MODEL PEMBELAJARAN KOOPERATIF NHT (NUMBERED HEAD TOGETHER) BERBANTUAN MIND MAPPING TERHADAP HASIL BELAJAR FISIKA PADA MATERI POKOK LISTRIK DINAMIS - Dede Parsaoran Damanik; Jelita Panjaitan; Ika Trisni Simangunsong (Jurnal Darma Agung, 2020)
This study aims at determining the significant influence of the NHT (Numbered Head Together) Cooperative Learning Model assisted by Mind Mapping on physics learning outcomes in the dynamic electric subject matter of class XII semester I students of SMK YAPIM TARUNA Sei Rotan. This type of research is a quasi experiment. The population in this study is all students of class XII SMK IAP YAPIM TARUNA. Sampling was done by cluster random sampling technique, then obtained class XII-1 = 35 people as an experimental class taught using the NHT (Numbered Head Together) Cooperative Learning model assisted by Mind Mapping and class XII-2 = 35 people as control classes taught by the Direct Learning model. This research instrument consisted of 25 multiple choice questions with 5 options (a, b, c, d, and e) which had previously been tested to determine the validity, reliability, level of difficulty and distinguishing power of the test. From the results of the study, an average value of experimental class pretest of 32.18 with a standard deviation of 9.49 and an average value of pretest of 31.18 with a standard deviation of 10.96 was obtained. From the results of the two-party t test obtained t count = 0.49 and t table = 1.99, because t count ˂ t table (0.49 <1.99) this shows that the initial ability of the two classes is the same. Then a different treatment was given. After the learning ended, posttest was done with the average value of the experimental class 73.18 with a standard deviation of 10.37 and the average value of the Control class 56.54 with a standard deviation of 11.94. The results of one-party t test obtained the price of tcount = 7.44 and ttable = 1.67 at the significant level α = 0.05 and dk = 86, because tcount ˃ ttable (7.44 ˃ 1.67), this shows that there is a significant influence significant NHT (Numbered Head Together) Cooperative learning model aided by Mind Mapping on physics learning outcomes on the subject matter of Dynamic Electricity